Perekonomian Indonesia Khususnya Pada Tingkat Makro - Rizky Ramadhani. P; Nurul Hasanah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The Indonesian economy at the macro level is the main focus in in-depth economic analysis. In this abstract, we explore the dynamics of the Indonesian economy on a macro scale, considering aspects such as economic growth, inflation, employment, and international trade. We use the latest data to provide a comprehensive picture of Indonesia's economic conditions in a global and regional context. In addition, we analyze the economic policies adopted by governments to respond to various economic challenges. The aim of this abstract is to provide in-depth insight into the Indonesian economy at a macro level, as well as highlight key aspects that need to be considered in efforts to improve national economic prosperity.